Software optimization of vision-based around view monitoring system on embedded platform - Mahamud, Nurul Hidayah; Zainal Abidin, Zulkifli; Mohd Zaki, Hasan Firdaus; Mohd Mustafah, Yasir; Sediono, Wahju; Abdul Rahman, Hasbullah; S., Hanizam; Abdul Matin, M. A. A.; Ahmad Rudin, Nurul Syuhada (SAE International Malaysia, 2020)
Image processing algorithm requires high computational power. Optimizing the algorithm to be run on an embedded platform is very critical as the platform provides limited computational resources. This research focused on optimizing and implementing a vision-based Around View Monitoring (AVM) system running on two embedded boards of Cortex-A7 quad and Cortex-A15 quad-core, and desktop platform of Intel i7 core. This paper presented a study on several techniques of software optimization that is removing code redundancy and multi-threading. The two methods improve the total processing time of the AVM system by 45% on ARM Cortex-A15 and 47% on ARM Cortex-A7.